Concurrent syphilis and Chlamydia trachomatis infection in bisexual male: A rare case of proctitis - Kumar, Naveen (J Family Med Prim Care, 2019)
Unsafe sexual practices in men who have sex with men population lead to emergence of high-risk networks for sexually transmitted infection transmission. The atypical clinical presentation of proctitis, the unawareness of physicians and patients in this regard, and the nonavailability of molecular diagnostic methods in routine practice may have contributed to its underdiagnosis. We report a case of syphilis in a bisexual male with a concurrent rectal Chlamydia trachomatis infection not previously reported from India. Reporting such cases has public health importance.